Religion as the Source of Reconciliation among Civilizations (American Journal of Islam and Society, 2002)
The problem of using the category of civilization in much of the social science literature is so obvious that it necessitates a philosophical definition. The heart of every civilization is its primordial tradition. The life of every civilization is tied to the well-being and operativeness of those religious truths that it upholds as sacred. When the religion dies, its civilization also dies. This paper points to the errant "clash of civilizations" thesis and argues that the seat of a universal ist consensus cannot be modernity. Rather, it must be religious traditions. It further argues that resuscitating the western tradition is a prerequisite for reconciliation between Islamic societies and the West, and finally, that the ideology of globalism is the wrong milieu for finding such a common platform.